Updates on the Management of Neurologic Complications of Post–Cardiac Arrest Resuscitation - Mayasi, Yunis; Geocadin, Romergryko G. (Seminars in Neurology, 2021)
Sudden cardiac arrest (SCA) is one of the leading causes of mortality and morbidity in the United States, and survivors are frequently left with severe disability. Of the 10% successfully resuscitated from SCA, only around 10% of these live with a favorable neurologic outcome. Survivors of SCA commonly develop post–cardiac arrest syndrome (PCAS). PCAS is composed of neurologic, myocardial, and systemic injury related to inadequate perfusion and ischemia–reperfusion injury with free radical formation and an inflammatory cascade. While targeted temperature management is the cornerstone of therapy, other intensive care unit–based management strategies include monitoring and treatment of seizures, cerebral edema, and increased intracranial pressure, as well as prevention of further neurologic injury. In this review, we discuss the scientific evidence, recent updates, future prospects, and knowledge gaps in the treatment of post–cardiac arrest patients.
Keywords: cardiac arrest; anoxic injury; post–cardiac arrest syndrome; secondary brain injury; outcomes